The Influence of Personal Selling and Price Perception on Customer Loyalty Through Customer Satisfaction as an Intervening Variable at Oriflame Sci Cianjur - Nurlaela, Ida; Diposumarto, Ngadino Surip; Pranowo, Agus Setyo (UNIVERSITAS PAKUAN, 2024)
Price perception and customer satisfaction together influence customer loyalty This research aims to determine the influence of personal selling and price perception on customer loyalty through customer satisfaction as an intervening variable at Oriflame SCI Cianiur. This research was conducted at Oriflame SCI Cianjur, with the hope that the results of this research can increase customer loyalty to Oriflame SCI Cianjur. In this study, sampling was used using Simple Random Sampline by distributing questionnaires to 133 members of Oriflame SCI Cianjur. Data from the questionnaire results were analyzed using SPSS Version 25 and Lisrel 8.80 software . The results of this research state that (1) personal selling has an impact on customer satisfaction, (2) price perception influences customer satisfaction, (3) personal selling influences customer loyalty. (4) price perception influences customer loyalty, (5) customer satisfaction influences customer loyalty, (6) personal selling and perception together influence customer satisfaction, (7) personal selling customer.